The RIPAT Manual rural initiatives for participatory agricultural transformation - Vesterager, Jens M.; The Rockwool Foundation (Copenhagen The Rockwool Foundation, 2013)
Sub-Saharan Africa remains the world's most food-insecure region in spite of the abundant agricultural potential. in an attempt to contribute towards overcoming this problem, a flexible agricultural extension approach known as RIPAT (Rural Initiatives for Particpatory Agricultural Transformation) has been developed over the period since 2006 through a series of projects in northern Tanzania. The RIPAT Manual explains step-by-step how to organise and implement a robust, group-based agricultural development project characterized by: HELP TO SELF-HELP-avoiding DONOR SYNDROME and ensuring that farmers take full charge of their own development the use of a group demonstration field, where RIPAT takes THE BEST FROM BOTTOM-UP AND TOP-DOWN EXTENSION APPROACHES giving farmers CHOICE regarding agricultural technologies and VOICE regarding how they want to organise their group and work together FORMALIZED COOPERATION with local government authorities and extension services for continuation and up-scaling.
Keywords: Agriculture